(untitled) (Philosophy and Progress, 2024)
Irresponsible carbon emissions by businesses are the leading factor in climate change, which are threatening human civilisation. Global leaders did little to curb industrialists’ authoritarianism despite calls from all concerned. Many researchers believe that business has an important role behind policymakers’ inaction. In this context, the main objective of this research is to explore the impact of business on climate policy when they shake hands or embrace with politics. This qualitative study used content analysis to meet the objective using primary data from Intergovernmental Panel on Climate Change, United Nations Framework Convention on Climate Change’s Conference of Parties decisions, and so on and secondary literature from books, dissertations, journals, and others. This study demonstrates that businesses have vehemently opposed climate science since its inception. When the issue became political in the 1980s, animosity intensified as they feared climate regulations would harm their interests. So, initially, they attempted to negate climate science by portraying it as something unproven and promoting climate change as an opportunity for humanity. They additionally applied a variety of strategies like publishing books, periodicals, research articles, and newspaper articles, spreading media propaganda, and giving donations to mislead policymakers. As a result, climate policy formation and implementation are significantly delayed, and business interests are protected. This study implies that businesses will suffer if civilisation collapses due to the unwise use of fossil fuels. Therefore, all stakeholders must prioritise collective interests over individual ones. Otherwise, it will engulf everyone. Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 151-182